(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2021)
A team is a group of people who work together to achieve a common goal. Virtual or remote teams can be defined as groups of geographically dispersed professionals, interconnected with each other through digital communication platforms, with the aim of carrying out a specific task indicated by the organization. Motivation is an important factor to be considered in the performance of virtual teams and this study presents stimulus factors based on scientific literature, applied to the virtual work scenario. The analysis carried out concludes that the same stimulus factors can be provided, both in the face-to-face and virtual work models, obtaining the same results. Keywords: Motivation; Virtual teams; Stimulus factors